Stemming engine for Bahasa Melayu words / Muhammad Aizat Abdul Rahman - Muhammad Aizat, Abdul Rahman (2006)
Despite its top rank in the world of the most speakers for a language. Bahasa Melayu is lacked in its computer software particularly in its language and grammar processing software. This situation had put much excite on me to build a system for stemming the words in Bahasa Melayu which can be used for further development of projects that will use Bahasa Melayu for its domain or in its interface. The purpose of this stemmer is to stem any given Bahasa Melayu words to its pure stem. The steps are, first, the system will take the input from user. Then, it will make a comparison in its database which is the dictionary of Bahasa Melayu stems. After that, in its stemming engine, the words will discard all the possible affixes that attached to it. Lastly, the pure stem of the word will be displayed as the output to the user. Another reason for me to build this system is to explore the power of programming in prolog which is one of the common languages for Artificial Intelligence. It is my hope that this project will give much help to those who concern about making Bahasa Melayu a prestigious language in the world.